Changes of regional mortality rates from cardiovascular diseases and cognitive disorders in Russia over 2019-2021 - I. V. Samorodskaya; M. A. Starinskaya; S. A. Boytsov (Российский кардиологический журнал)
Aim. To analyze mortality from cardiovascular diseases (CVDs) and diseases associated with cognitive impairment (CI) in the regions of the Russian Federation.Material and methods. We analyzed Rosstat mortality data in 82 Russian regions in mid-year population in one-year age groups for 2019-2021. Eleven groups of causes have been formed, standardized mortality rates (SMRs), average regional SMRs, and their changes over time was assessed.Results. In total, SMRs from CVD and CI increased from 551,4±84,9 in 2019 to 622,6±98,5 per 100 thousand population in 2020 and decreased in 2021 to 612,6±106 per 100 thousand population. However, its proportion in all-cause mortality decreased by almost 10% (46,97±4,6 in 2021 and 55,98±4,6% in 2019). The growth of SMRs from year to year was noted in 30 regions; in other regions, unstable changes were noted. The proportion of CVD causes from all-cause mortality was 30,5±5,8% in 2019, 29,1±5,7% in 2020 and 25,95±5,56% in 2021 (p<0,0001). The largest SMRs and their proportion in the mortality structure are in group 1 (chronic coronary artery disease (CAD) — an average of 17,8±5,8% over 3 years) and group 6 (causes with unclear criteria for the disease, but associated with CI — 13,9±5,9%). The contribution of the second (acute coronary artery disease — 4,6±2,8%), the third (defects, cardiopathies, endo- and myocarditis — 4,8±2,7%) and the fifth (stroke — 6,1±1,7%) groups of causes are much smaller. The sixth place in terms of SMRs and contribution to all-cause mortality is occupied by alcohol-associated causes (1,8±1,1%). The proportion of other causes (hypertension, Alzheimer’s disease, Parkinson’s disease, other mental disorders) is small.Conclusion. When developing and implementing programs aimed at reducing mortality, results obtained should be taken into account. Significant regional differences in the rate and changes of SMRs over time indicate the need to unify the criteria for the underlying cause of death, especially in multimorbid patients.